Design of Expelling Machine for Briquettes Made of Obtained Bio-Chars from Cashew Nut Shells’ Pyrolysis - GODJO, THIERRY; VISSOH, LÉANDRE MATHIAS; Guidi, Clotilde; ADOMOU, ALAIN ALEXIS COMLAN NICAISE; SANYA, EMILE ADJIBADÉ (My University, 2016)
In the context of densification of biochar made from cashew nut shells’ pyrolysis, the University Institute of Technology of Lokossa has successively developed two small scale equipments: a manual lever press and a hydraulic press. Although both the developed equipments had significant densification rates (81% and 85% respectively for manual lever press and hydraulic press), it remains to enhance the throughput (10 kg/hr and 90 kg/hr respectively for manual lever press and hydraulic press).This paper presents the design of an efficient Expelling Machine for Briquettes made from cashew nut shells pyrolysis biochars. The machine has been designed to a capacity of 500 kg/hr and can expel briquettes at the rate of 1,000 briquettes/hr. The machine is powered using electric motor of 7 kW to be operated for 8 working hours. This machine improves the performances of existing briquetting technologies and it will enhance the environmental footprint. - See more at: http://www.journalijar.com/article/13558/design-of-expelling-machine-for-briquettes-made-of-obtained-bio-chars-from-cashew-nut-shells/-pyrolysis/#sthash.yc66mJo9.dpuf
Keywords: Cashew Nut Shell; Briquettes; Expelling; Machine Design; Benin